A cost effectiveness analysis within a randomised controlled trial of post-acute care of older people in a community hospital. Issue 7561 (21st July 2006) - O'Reilly, Jacqueline; Lowson, Karin; Young, John; Forster, Anne; Green, John; Small, Neil
Abstract: Objective To assess the cost effectiveness of post-acute care for older people in a locality based community hospital compared with a department for care of elderly people in a district general hospital, which admits patients aged over 76 years with acute medical conditions. Design Cost effectiveness analysis within a randomised controlled trial. Setting Community hospital and district general hospital in Yorkshire, England. Participants 220 patients needing rehabilitation after an acute illness for which they required admission to hospital. Interventions Multidisciplinary care in the district general hospital or prompt transfer to the community hospital. Main outcome measures EuroQol EQ-5D scores transformed into quality adjusted life years (QALYs), and health and social service costs over six months from randomisation. Results The mean QALY score for the community hospital group was marginally non-significantly higher than that for the district general hospital group (0.38 v 0.35) at six months after recruitment. The mean (standard deviation) costs per patient of the health and social services resources used were similar for both groups: community hospital group £7233 (euros 10 567; $13 341) (£5031), district general hospital group £7351 (£6229), and these findings were robust to several sensitivity analyses. The incremental cost effectiveness ratio for community hospital care dominated. A cost effectiveness acceptability curve, based on bootstrapped simulations, suggests that at a willingness to pay threshold of £10 000 per QALY, 51% of community hospital cases will be cost effective, which rises to 53% of cases when the threshold is £30 000 per QALY. Conclusion Post-acute care for older people in a locality based community hospital is of similar cost effectiveness to that of an elderly care department in a district general hospital.